Molecular Endophenotypes of Mood and Schizophrenia in Mice - Huuskonen, Sini (My University, 2020)
JNK pathway inhibition has been shown to reduce anxiety-like behaviour in rodent models. However, the JNK pathway is also implicated in schizophrenia and precisely how, is still unknown. To gain basic understanding on how JNK1 effects neural activity in brain, we examined c-fos expression in hippocampus of wild type and Jnk1-/- mice. We also examined how this expression changes in response to an NMDA antagonist, MK-801. To study this we used immunohistochemistry for c-fos staining method and did correlative behavioural testing. It was seen that Jnk1-/- mice had significantly higher c-fos positive nuclei count compared to control C57BL/J6 mice in dentate gyrus granule cell layer in hippocampus. Interestingly, after treatment of Jnk1-/- mice with 0.4 mg/kg MK-801, c-fos expression significantly dropped in dentate gyrus granule cell layer, whereas c-fos in control mice was unaffected by MK-801. Behaviourally, Jnk1-/- mice, showed notably less anxiety and depressive-like behaviour when compared to wild type mice as previously reported by our group, and MK-801 treatment caused disturbed behaviour, namely hyperactivity, but no change in anxiety or depressive like behaviour was seen. Wild type mice also showed hyperactive behaviour following MK-801 treatment, as expected. These results are consistent with Jnk1-/- mice displaying hippocampal disinhibition.
Keywords: c-Jun N-terminal kinase, Schizophrenia, MK-801, Mouse model